Efeito de partículas de desgaste no comportamento tribológico de metais - Oliveira Júnior, Mario Martins de (2018)
The literature is controversial in relation to the influence of wear debris on tribological behaviour. Some works have shown that the presence of debris is fundamental to the formation of a protective tribolayer, thus reducing friction and wear, whereas others showed that the presence of wear debris could contribute to increase friction coefficient due to the energy spent dragging them into the contact. This work aims to study the influence of wear debris on tribological behaviour of metals. Tests under reciprocating wear sliding contact with debris removal (by compressed air flow), without removal and with the addition of iron oxides and alumina particles were performed. The pre-tests with debris removal showed a significant reduction in friction and wear, however, the contact was contaminated by the debris removal system. Testes performed after the compressed air treatment showed results completely different. The tests with the addition of iron oxide particles resulted in friction (15%) and wear (95%) reduction when added the Fe3O4 particles (larger and softer) suggesting that their relative hardness in relation to the materials in contact was the main factor for this reduction. Dry tests with addition of alumina particles on aluminum samples resulted in an increase in friction and wear when the small particles were added. The controlled addition of alumina particles contributed to a decrease in the counter bodies wear rate when the larger particles were added. The addition of alumina particles dispersed in distilled water contributed to a significant reduction in friction when the larger particles were added. These large particles intensified significantly the formation of a tribolayer on the sample surface, which resulted in a gain of mass. It was proposed a new index, called Relative Size (RS), comparing the sizes of the wear debris and the specimen surface roughness. For RS values less than 1, the wear debris was too small to get involved in the tribological contact and they did not affect friction and wear. For larger RS values, the particles participated actively in the formation of a protective tribolayer, reducing friction and the system wear. The increase in the concentration of alumina particles added in the contact contributed to an increase in friction and wear. Therefore, the presence of debris in contact is beneficial since the addition of particles contributed, in the majority of cases, to reductions on friction and wear.